2000
DOI: 10.1128/jb.182.11.3292-3297.2000
|View full text |Cite
|
Sign up to set email alerts
|

Organization, Structure, and Variability of the rRNA Operon of the Whipple's Disease Bacterium ( Tropheryma whippelii )

Abstract: Whipple's disease is a systemic disorder associated with a cultivation-resistant, poorly characterized actinomycete, Tropheryma whippelii. We determined a nearly complete rRNA operon sequence of T. whippelii from specimens from 3 patients with Whipple's disease, as well as partial operon sequences from 43 patients. Variability was observed in the 16S-23S rRNA spacer sequences, leading to the description of five distinct sequence types. One specimen contained two spacer sequence types, raising the possibility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
56
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 30 publications
7
56
0
3
Order By: Relevance
“…Furthermore, a recent study has indicated that two different genotypes could be detected in the same clinical specimen (18), thereby introducing the possibility of cross-contamination and thus the determination of erroneous sequences when infected tissues are examined directly. The availability of the first T. whippelii isolate (27) has allowed us to apply the genome walking strategy (32) to the accurate determination of gene sequences in this emerging bacterial species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent study has indicated that two different genotypes could be detected in the same clinical specimen (18), thereby introducing the possibility of cross-contamination and thus the determination of erroneous sequences when infected tissues are examined directly. The availability of the first T. whippelii isolate (27) has allowed us to apply the genome walking strategy (32) to the accurate determination of gene sequences in this emerging bacterial species.…”
mentioning
confidence: 99%
“…Taxon-specific 16S rDNA primers have since been used to detect the bacterium in patients (28,39) and sewage effluent (17), while sequence analysis of the 16S-23S rDNA spacer was used for the differentiation of strains into three different groups on the basis of their genotypes (9). Two additional genotypes were also subsequently described (18).…”
mentioning
confidence: 99%
“…In 1991, Wilson et al used broad-range primers to amplify bacterial 16S rDNA directly from infected tissue and then determined that this bacterium belongs to the high-GϩC-content, gram-positive bacteria among the class Actinomycetes (36). To date, six genotypes (numbered 1 to 6) of T. whipplei have been described based on sequence variation within the 16 to 23S ribosomal DNA (rDNA) intergenic spacer, and two genotypes (named A and B) have been described based on the 23S rRNA gene (14)(15)(16)25).…”
mentioning
confidence: 99%
“…The diagnosis of Whipple's disease is usually based on the presence of diastase-resistant non-acidfast periodic acid Schiff (PAS)-positive inclusions in macrophages of intestinal biopsies or by electron microscopy showing the trilamellar membrane of T. whipplei (6). Since the sequences of the rRNA genes are known (14,15,22,28), several PCR systems have been developed to identify parts of its 16S ribosomal DNA (rDNA) (2,4,23), of the 16S-23S rDNA internal transcribed spacer (ITS) (12), or of the 23S rDNA (13). These DNA amplification methods are more sensitive than histopathological analysis.…”
mentioning
confidence: 99%